Lichen planus pemphigoides in a child - Mariame Meziane; Siham Lakjiri; Taoufik Harmouch; Ouafae Mikou; Fatima Zahra Mernissi (Wolters Kluwer Medknow Publications, 2014)
Introduction: Lichen planus pemphigoides (LPP) is a rare autoimmune subepidermal blistering disease characterized by evolution of vesico-bullous skin lesions in patients with active lichen planus. We describe a case of LPP in a 12-year-old girl with clinical, histological and direct immunofluorescence findings. Case report: A 12-year-old Moroccan girl presented, after sun burn, pruritic violaceus papules on hands and feet complicated by the apparition of bullous lesions on apparent normal skin and on lichenoid eruption. A white reticulated pattern was present on the oral mucosa. Histopathology of lichenoid papule and bulla was consistent with the diagnosis of LPP. Direct immunofluorescence of peribullous skin showed linear deposits of IgG and C3 at the basal membrane zone. Treatment with Dapsone was successful. Discussion: LPP is exceptional in children; just fifteen cases were reported in the literature. This condition seems to be idiopathic. However, in rare cases it has been associated with some drugs or after PUVA therapy. In our patient, it was probably induced by prolonged sun exposure.